2008
DOI: 10.1021/la801419k
|View full text |Cite
|
Sign up to set email alerts
|

Electrohydrodynamic Flow and Colloidal Patterning near Inhomogeneities on Electrodes

Abstract: Current density inhomogeneities on electrodes (of physical, chemical, or optical origin) induce long-range electrohydrodynamic fluid motion directed toward the regions of higher current density. Here, we analyze the flow and its implications for the orderly arrangement of colloidal particles as effected by this flow on patterned electrodes. A scaling analysis indicates that the flow velocity is proportional to the product of the applied voltage and the difference in current density between adjacent regions on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 29 publications
(41 reference statements)
0
43
0
Order By: Relevance
“…Previous investigations have shown that colloidal patterning can occur on the surface of planar ITO due to inhomogeneous current densities when the ITO film is altered physically 20 or with applied ultraviolet illumination. 16 For our experiments, nanoparticle aggregation occurred not only on the surface of ITO, but on gold as well.…”
Section: Image Acquisition and Analysismentioning
confidence: 99%
“…Previous investigations have shown that colloidal patterning can occur on the surface of planar ITO due to inhomogeneous current densities when the ITO film is altered physically 20 or with applied ultraviolet illumination. 16 For our experiments, nanoparticle aggregation occurred not only on the surface of ITO, but on gold as well.…”
Section: Image Acquisition and Analysismentioning
confidence: 99%
“…EHD flow, a second mechanism, is one form of fluid flow that is induced by the mutual attraction which an applied electric field exerts on ions in a fluid. According to studies by Fagan et al and Green et al, the flow affects the motion of particles on an electrode surface in an AC frequency region above 500 Hz [119][120][121][122][123][124][125][126]. It gathers the particles laterally, lifting them up slightly from the electrode surface.…”
Section: Opto-electrokinetic Physics Of Repmentioning
confidence: 99%
“…Of course, since the first demonstration of self healing behaviour via the liquid healing agent route, alternative routes have been identified to induce self healing behaviour such as elastic recovery in combination with reversible physical networks as employed in ionomers ], reversible hydrogen and other chemical bonds as employed in supra molecular materials [Sijbesma et al 1997], crack jamming by transport of particles under the influence of an electrical field [Ristenpart 2008], long distance reptation of dissolved linear molecules in a thermoset matrix [Hayes 2007], atomistic diffusion followed by local formation of strengthening precipitates in aluminium alloys [Lumley 2003], local oxidation of the crack zone leading to the formation of new phases with a higher specific volume as in a very special high temperature ceramic [Song et al 2008] volumetric expansion of a nanostructure clay micro-layer to fill cracks in a multilayered coating [Micciche 2008, Hikasa 2004, and finally local deposits in the crack surface of bio-concrete grades due to bacterial excrements . In all the above examples the matrix is the more rigid phase and the healing agent is the mobile, i.e.…”
Section: Introductionmentioning
confidence: 99%